Handbook of Gender Research in Psychology Volume 1: Gender Research in General and Experimental Psychology - Chrisler, Joan C.; McCreary, Donald R.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
A major milestone in psychology has been the shift from concepts of sex, a strictly biological construct, to gender, with its range of biopsychosocial dimensions. Accordingly, recent years have seen gender research achieve marked improvements in methods, terminology, and breadth of content. The Handbook of Gender Research in Psychology brings these achievements into bold perspective by presenting both the current state of the field and an ambitious agenda for the future. Volume 1, Gender Research in General and Experimental Psychology, gathers a wide variety of established and emerging voices across the range of specialties to offer the latest ideas, theories, and findings in gender as applied to both women and men (and where appropriate, boys and girls), including sexual minorities. In this volume, contributors critique strengths and limitations of current research, discuss methodological issues from recruiting participants to communicating results, and address cultural and other diversity considerations that have often been absent from the field. Their findings offer a fresh perspective, whether readers are involved in testing hypotheses, developing models, conducting experiments, or interpreting data. All chapters include recommendations for future avenues for research. Areas covered in Volume 1: The history of the psychology of women, men/masculinity, and sexual minorities Qu antitative and qualitative research methods, including reviews of commonly used measures The brain and behavior: physiology and beyond Learning, education, and cognition, including academic, spatial, and creative abilities Written, oral, and nonverbal communication Emotion, motivation, and sexuality Gender roles and identity across the lifespan Psychologists, neuroscientists, gender researchers, and professors and graduate students in related fields will welcome Volume 1 of the Handbook of Gender Research in Psychology as refreshingly informative and eminently practical.
History of Psychology -- Emergence and Development of the Psychology of Women -- Emergence and Development of the Psychology of Men and Masculinity -- Emergence and Development of the Psychological Study of Lesbian, Gay, Bisexual, and Transgender Issues -- Research Methods -- Quantitative Approaches to the Study of Gender -- Qualitative Inquiry in Gender Studies -- Measuring Gender: Options and Issues -- Cross-Cultural Research Methods and the Study of Gender -- Gender Diverse Recruitment to Research Projects -- Interpreting and Communicating the Results of Gender-Related Research -- Brain and Behavior -- The Physiology of Sex Differences -- Sex and Gender in Sensation and Perception -- On Tending to Our Scientific Knitting: Thinking About Gender in the Context of Evolution -- Learning, Education, and Cognitive Processes -- Gender in the Classroom -- Gender and Academic Abilities and Preferences -- Gender, Spatial Abilities, and Wayfinding -- Gender and Creativity -- Communication -- Words Matter: The Language of Gender -- She Said, He Said: Gender, Language, and Power -- Gender, Power, and Nonverbal Behavior -- Emotion and Motivation -- Gender, Emotion, and Socialization -- Sex and Gender Differences in Eating Behavior -- Gender Differences in Sexuality -- Lifespan Development -- Gender Identity and Stereotyping in Early and Middle Childhood -- Gender in Adolescence: Applying a Person-in-Context Approach to Gender Identity and Roles -- Gender, Adult Development, and Aging.
Keywords: Psychology; Psychotherapy; Sociology; Sex (Psychology).; Gender expression; Gender identity; Psychology; Gender Studies; Sociology, general; Psychotherapy; Electronic books